EDUCATION ON THE USE OF THE ENVIRONMENT IN AN EFFORT TO ANTICIPATE VILLAGERS TERANTANG TO FACE THE COVID-19 PANDEMIC - mira mira mira (Borneo Community Development, 2021)
Corona virus 2019 (Covid-19) is a disease caused by the corona virus which has caused a global health crisis and has had a major impact on daily life. Prevention of the transmission of Covid 19 in Barito Kuala, especially in the Mandastana sub-district, has been running, but because awareness to maintain environmental cleanliness is still very low, it has an impact on other problems that ariseThis community service activity plays an important role in helping government programs to prevent the transmission of COVID-19 by maintaining and utilizing environmental cleanliness, reducing waste and the impact on environmental pollution such as floods. The team carried out environmental utilization education in an effort to anticipate villagers who were challenged to face the Covid-19 pandemic. The result of this service was that the knowledge of Terentang residents about preventing Covid-19 by utilizing environmental hygiene had increased, but to dispose of waste and how to manage it still needed to be improved. Most of the residents have done what the team has said, but education still needs to be carried out to increase knowledge, increase awareness and be more active in preventing Covid-19 and keeping the environment clean.